Prospects for Sub-Micron Solid State Nuclear Magnetic Resonance Imaging with Low-Temperature Dynamic Nuclear Polarization - Thurber, Kent R. (2010)
We evaluate the feasibility of (1)H nuclear magnetic resonance (NMR) imaging with sub-micron voxel dimensions using a combination of low temperatures and dynamic nuclear polarization (DNP). Experiments are performed on nitroxide-doped glycerol/water at 9.4 T and temperatures below 40 K, using a 30 mW tunable microwave source for DNP. With DNP at 7 K, a 0.5 µl sample yields a (1)H NMR signal-to-noise ratio of 770 in two scans with pulsed spin-lock detection and after 80 db signal attenuation. With reasonable extrapolations, we infer that (1)H NMR signals from 1 µm(3) voxel volumes should be readily detectable, and voxels as small as 0.03 µm(3) may eventually be detectable. Through homonuclear decoupling with a frequency-switched Lee-Goldburg spin echo technique, we obtain 830 Hz (1)H NMR linewidths at low temperatures, implying that pulsed field gradients equal to 0.4 G/d or less would be required during spatial encoding dimensions of an imaging sequence, where d is the resolution in each dimension.